Pengaruh Pemberian Jus Wortel Berastagi Terhadap Intensitas Nyeri Haid (Dismenorea Primer) Pada Remaja Putri - Ayuningtyas, Berlian; Widya Keswara, Nila; Safitri, Rani (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Primary dysmenorrhea is a health problem frequently experienced by adolescent girls during menstruation and can disrupt daily activities. Menstrual pain occurs due to increased prostaglandin production, which causes excessive uterine contractions. Pharmacological therapy is generally used for treatment, but continued use of medication can cause side effects. Therefore, safe non-pharmacological alternatives are needed, one of which is consuming carrot juice. Carrots (Daucus carota L.) contain beta-carotene, vitamin A, vitamin E, and antioxidants that can help reduce inflammation and inhibit prostaglandin production, potentially reducing the intensity of menstrual pain. This study aims to determine the effect of Berastagi carrot juice on the intensity of menstrual pain (primary dysmenorrhea) in adolescent girls at SMPN 1 Tumpang, Malang Regency. The study used a quasi-experimental design with a pretest–posttest control group design. The study sample consisted of 30 respondents divided into intervention and control groups using a purposive sampling technique. Pain intensity was measured using a pain scale before and after the intervention. Data analysis used statistical tests with a significance level of p < 0.05. The results of the study showed a decrease in menstrual pain intensity in the group given Berastagi carrot juice, with a statistical test result showing a p-value of 0.000 (p < 0.05). The conclusion of this study is that administering Berastagi carrot juice has an effect on reducing menstrual pain intensity in adolescent girls.